2007
DOI: 10.1590/s0066-782x2007001700001
|View full text |Cite
|
Sign up to set email alerts
|

Peso dos ventrículos cardíacos determinado em necropsia de indivíduos saudáveis mortos por causas externas

Abstract: SummaryObjective: To establish cardiac ventricular weights recorded during the autopsy of healthy individuals who died of external causes, aiming at determining normality patterns in our population. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The study did not include measurements of the atrial and right ventricle mass as this was not possible due the thin walls of these structures. However, our previous studies indicated no changes in pro-atrial-natriuretic factor during maximum apnea in competitive BHD indicating no stretching of atrial muscle, and as the right ventricle is much less muscular than the left (Rodrigues et al, 2007), we assume that changes in these chambers may be of lesser importance (Kjeld et al, 2015;Kjeld et al, 2021c). Measurements were all done during dry apneas after glossopharyngeal insufflation, which limits venous return (Eichinger et al, 2010).…”
Section: Limitationsmentioning
confidence: 98%
“…The study did not include measurements of the atrial and right ventricle mass as this was not possible due the thin walls of these structures. However, our previous studies indicated no changes in pro-atrial-natriuretic factor during maximum apnea in competitive BHD indicating no stretching of atrial muscle, and as the right ventricle is much less muscular than the left (Rodrigues et al, 2007), we assume that changes in these chambers may be of lesser importance (Kjeld et al, 2015;Kjeld et al, 2021c). Measurements were all done during dry apneas after glossopharyngeal insufflation, which limits venous return (Eichinger et al, 2010).…”
Section: Limitationsmentioning
confidence: 98%
“…However, distortions are more likely to occur in such situations since, depending on the time elapsed and clinical condition of the patient before death, the bias can be relevant. In our midst, Rodrigues et al 29 studied hearts from autopsies of healthy individuals who died of accidental causes and suggested the presence of LVH when the left ventricular mass is higher than 218g or 128 g/m in men and 148 g or 88 g/m in women.…”
Section: Original Articlementioning
confidence: 99%
“…De Marco et al relatam resultados de monitorização residencial de pressão arterial, sem correlação entre a PAD e o IMVE. A PAS e a PP correlacionam-se positivamente com o IMVE (33) . Machado et al caracterizaram cuidadores de candidatos a transplante do coração e identificaram um familiar (cônjuge), do sexo feminino, com idade média de 44,3 anos, renda própria, classificados, na maioria, como "bons" ou "regulares", não havendo correlação com escolaridade, atividade profissional e renda (34) .…”
Section: Cardiologiaunclassified